ANALISIS DETERMINAN HARGA SAHAM PADA SUB SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Nurkholik Nurkholik; Rezki Diah Kristianti (Faculty of Economic and Business Universitas STIKUBANK, 2021)
This study aims to determine the relathionship between Net Profit Margin (NPM), Return On Investment (ROI), Return On Equity (ROE), Earning Per Share (EPS), and Dividend Per Share (DPS) to Stock Price. Population in this reseach is large tranding sub-sector food and bevarages on the Indonesian Stock Exchange during 2015 until 2018 period. Technique of sampling in this reseach using purposive sampling with a total sample based on criteria is 44. The results of the study indicate that partially Net Profit Margin (NPM) has positive affect the stock price, Return On Investment (ROI) has significant negative affect the stock price, Return On Equity (ROE) has positive affect the stock price, Earning Per Share (EPS) has significant negative affect the stock price, and Dividend Per Share (DPS) has positive affect the stock price. Keywords: stock price, net profit margin), return on investment, return on equity, earning per share, and dividend per share